Histone acetyltransferase 1 upregulates androgen receptor expression to modulate CRPC cell resistance to enzalutamide. Issue 7 (22nd July 2021) - Hong, Zhe; Xiang, Zhendong; Zhang, Pan; Wu, Qiang; Xu, Chengdang; Wang, Xinan; Shi, Guowei; Hong, Zongyuan; Wu, Denglong
Abstract: Castration‐resistant prostate cancer (CRPC) is the latest stage of PCa, and there is almost no effective treatment available for the patients with CRPC when next‐generation androgen deprivation therapy drugs, such as enzalutamide (ENZ), fail. The androgen receptor (AR) plays key roles in PCa and CRPC progression and drug resistance. Histone acetyltransferase 1 (HAT1) has recently been reported to be highly expressed in some tumors, such as lung carcinoma. However, what relationship between the AR and HAT1, and whether or how HAT1 plays roles in CRPC progression and drug resistance remain elusive. In the present study, we found that HAT1 is highly expressed in PCa cells, and the overexpression of HAT1 is linked with CRPC cell proliferation. Moreover, the HAT1 expression is positively correlated with the expression of AR, including both AR‐FL (full‐length) and AR‐V7 (variant 7), which is mainly mediated by a bromodomain containing protein 4 (BRD4) ‐mediated pathway. Furthermore, knockdown of HAT1 can re‐sensitize the response of CRPC cells to ENZ treatment in cells and mouse models. In addition, ascorbate was observed to decrease AR expression through downregulation of HAT1 expression. Collectively, our findings reveal a novel AR signaling regulation pathway in PCa and CRPC and suggest that HAT1 serves as a critical oncoprotein and an ideal target for the treatment of ENZ resistance in CRPC patients. Abstract : HAT1 is highly expressed in PCa cells and correlated with PCa and CRPC progression. AR is transcriptionally upregulated by HAT1 through a BRD4‐madiated pathway. Knockdown of HAT1 re‐sensitizes CRPC cells to enzalutamide treatment.